Selected Philippine plant extracts as alternative preservatives for a pharmaceutical liquid preparation - Arollado, Erna C.; Bucog, Leslie P.; Manalo, Richelle Ann M.; Sampang, Irizh-Lyn R.; Cariscal, Janvin Jessel A. (2017)
Preservatives play an essential role in enhancing quality and prolonging shelf-life of pharmaceutical products by improving their antimicrobial stability or reducing the amounts of oxidative degradation products. Persistent use of synthetic compounds as preservatives resulted in several reports of undesirable effects. Hence, development of alternatives is necessary to maintain their vital function while minimizing adverse effects. In this study, ethanolic extracts of five plants with known antimicrobial activities, Psidium guajava, Premna odorata, Mimosa pudica, Allium sativum and Zingiber officinale, were formulated into suspensions and evaluated for preservative activity using the United States Pharmacopeia (USP) (2015) guidelines. Phytochemical test, antioxidant activity and compatibility test were also conducted on the extracts. Premna odorata (p=0.999) and Mimosa pudica (p=0.054) at 5.00 mg/mL concentration exhibited comparable antioxidant activity against the standard antioxidant preservative, butylated hydroxytoluene, using ferric reduction antioxidant power assay. Based on the criteria for product category 4 of the USP, suspensions of Premna odorata and Psidium guajava demonstrated acceptable preservative activity against selected microorganisms, Escherichia coli and Staphylococcus aureus. These bioactivities can be attributed to the phytochemicals present in the extracts such as glycosides, reducing substances, flavonoids and alkaloids. In conclusion, for the USP category 4 products such as antacid suspensions, Psidium guajava can be utilized as an alternative source of antimicrobial preservative, Mimosa pudica as an alternative source of antioxidant preservative, and Premna odorata as an alternative source of preservative with both antimicrobial and antioxidant efficacy.